GENETICS OF PHOSPHORUS, POTASSIUM, MAGNESIUM AND CALCIUM CONTENT FOR BARLEY GRAIN IMPROVEMENT - Dragan Perovic; Marija Kraljevic-Balalic; Igor Balalic; Milivoje Milovanovic; Jelena Milivojevic; Gordana Surlan-Momirovic; V. Vujacic; S. Prodanovic; Irena Radinovic (Journal of Animal and Plant Sciences, 2025)
Studying the inheritance of phosphorus (P), potassium (K), magnesium (Mg), and calcium (Ca) in barley grains is important because it enables the improvement of nutritional quality and crop yields through crop breeding. The aim of this study was to determine, through the application of diallel analysis, the mode of inheritance and components of genetic variance of P, K, and Mg in barley grains, as well as the combining abilities of the experimental material for these macroelements. The study was conducted at the experimental field of the Center for Small Grains in Kragujevac, Serbia.The plant material consisted of twelve F1 hybrids resulting from a complete diallel cross between four winter barley varieties (Partizan, KG-6, HVW-247, NS-293). Hybridizations were performed through manual pollination, and the resulting F1 hybrids, along with their parents, were sown in a randomized block design with three replications. The content of macroelements (P-phosphorus, K-potassium, Mg-magnesium and Cа-calcium) was quantified in the grain of the parents and the F1 generation. Narrow sense heritability was highest for the potassium content (72.21%) and lowest for the magnesium (14.45%). The general combining ability (GCA) and the specific combining ability (SCA) were determined for the parents and the hybrids, respectively. The inheritance of the P and K content was mainly influenced by the additive genetic component, while the inheritance of Mg was predominantly influenced by the dominant genetic component. For Ca content, the additive-dominant inheritance model was not satisfactory due to inter-allelic interaction. VrWr regression analysis followed the previously established models of inheritance. The variety KG-6 was identified as the best general combiner for P, Mg, and Ca content, while NS-293 was found to be the best general combiner for K and Mg content in barley grains. These varieties can be effectively utilized as gene donors for enhancing the mineral composition in future F1 hybrids.
Keywords: Hordeum vulgare L.; diallel analysis; macroelements; regression analysi